2015
DOI: 10.1016/j.jlumin.2014.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Light emitting diode based on n-Zn0.94M0.06O nanorods/p-GaN (M= Cd and Ni) heterojunction under forward and reverse bias

Abstract: In this study, we report on the improvement in the optoelectronic properties of n-ZnO nanorods/p-GaN heterojunction. This was achieved by doping the ZnO with cadmium (Cd) and nickel (Ni). The ZnO and Zn0.94M0.06O nanorods grown hydrothermally on the p-GaN substrate were used to fabricate the light emitting diodes (LEDs). Structural measurement revealed that nanorods with wurtzite structure having a preferential orientation along the (002) c-axis. The UV-vis spectra show that the optical band gap of Zn0.94M0.06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In order to bypass the challenging p-type doping of wide bandgap MgZnO, the MgZnO-based heterostructures have been extensively studied by employing p-GaN as the holetransporting layer recently. [15,[33][34][35] In 2009, Zhu et al reported on the fabrication of an n-Mg 0.12 Zn 0.88 O/p-GaN heterojunction LED with an MgO dielectric interlayer by plasmaassisted molecular beam epitaxy technique. [34] By the proper engineering of the band alignment of the heterojunction with using the MgO layer, most electrons are confined in the Mg 0.12 Zn 0.88 O layer under positive bias, while holes can be injected into the Mg 0.12 Zn 0.88 O active layer from the p-GaN side, and the typical EL spectra from the heterostructure are shown in Fig.…”
Section: N-mgzno-based Heterojunction Duv Ledsmentioning
confidence: 99%
“…In order to bypass the challenging p-type doping of wide bandgap MgZnO, the MgZnO-based heterostructures have been extensively studied by employing p-GaN as the holetransporting layer recently. [15,[33][34][35] In 2009, Zhu et al reported on the fabrication of an n-Mg 0.12 Zn 0.88 O/p-GaN heterojunction LED with an MgO dielectric interlayer by plasmaassisted molecular beam epitaxy technique. [34] By the proper engineering of the band alignment of the heterojunction with using the MgO layer, most electrons are confined in the Mg 0.12 Zn 0.88 O layer under positive bias, while holes can be injected into the Mg 0.12 Zn 0.88 O active layer from the p-GaN side, and the typical EL spectra from the heterostructure are shown in Fig.…”
Section: N-mgzno-based Heterojunction Duv Ledsmentioning
confidence: 99%
“…Also, two broad deep level emission (DLE) peaks were observed for the ZnO nanorods and were extended approximately from 1.80 eV to 2.08 eV (DLE1, red emission) and from 2.09 eV to 2.86 eV (DLE2, green emission). The green and red emissions are ascribed to the recombination of electron-hole pairs between the conduction band or zinc interstitial (Zni) energy level to oxygen vacancy (VO) and oxygen interstitial (Oi) energy level, respectively [28,29]. To investigate the optical quality of the pure and doped ZnO nanorods, the intensity ratio INBE/IDLE was measured, and is demonstrated in Figure 3(b), where INBE and IDLE are the integrated intensity of the NBE and the DLE peaks, respectively.…”
Section: Optical Propertiesmentioning
confidence: 99%